The Role of Dual Antiplatelet in Stent-Assisted Coiling in Wide-Neck Aneurysm - Ricky Gusanto Kurniawan; Bambang Tri Prasetyo; Beny Rilianto; Abrar Arham (Universitas Airlangga, 2023)
Highlight: Dual antiplatelet is the gold standard for endovascular treatment of wide-neck aneurysms. The role of dual antiplatelet is to prevent stent thrombosis after treatment. The thrombosis rate reported during stent-assisted coiling is quite high. ABSTRACT Stent-assisted coiling (SAC) in wide-neck aneurysm treatment is associated with antiplatelet use. Dual antiplatelet therapy (DAPT) has been the gold standard for protecting against thrombosis events and is widely accepted for endovascular embolization treatment with a stent-assisted or flow diverter. Some patients experience vascular events due to the reduced efficacy of antiplatelet agents despite taking DAPT. The reported thrombosis rates during stent-assisted coiling embolization range from 2% to 20%. Thromboembolic complications, such as in-stent thrombosis, can manifest in 4.6% of cases. The correlation between platelet reactivity during treatment and bleeding events remains unclear. However, the association between High Residual Platelet Reactivity (HRPR) or hyporesponsiveness and ischemic events is well established. Based on various laboratory definitions, hyperresponsiveness in patients with clopidogrel occurs in about 14–30% of patients due to major and minor bleeding. Therefore, the optimization of antiplatelet therapy has developed significantly in the neurointerventional community.